SPEECH ACTS ANALYSIS OF PRESIDENT OBASANJO’S ENDORSEMENT LETTER OF MR. PETER OBI’S PRESIDENTIAL CANDIDACY (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2023)
Every form of human communication is driven by intentions and the need to unearth such intentions which usually lie beyond the statement is the duty of pragmatic linguistic research. This paper examines the 1st January 2023 endorsement/open letter of President Olusegun Obasanjo to all Nigerians wherein, in the midst of a keenly contested presidential election in Nigeria, Obasanjo in that letter, openly made a choice of Mr. Peter Obi, the presidential candidate of the Labour Party against other contestants from other political parties. The research sought to find out the rationale behind the linguistic choices made in the letter. With particular interest in Searle’s typology, Speech Act Theory was employed in the research. Quantitative research alongside the descriptive survey methodology was adopted for the analysis of data. The research question of whether indirectness in Speech Act can also carry illocutionary force was raised and answered and it constitutes the research gap this work filled. Findings reveal a preponderance of the Representative Acts in the Direct Speech Acts which is a testament that Obasanjo, the writer, is committed to the truth of proposition and a preponderance of the Directives in the Indirect Speech Acts which means that his message in the letter is indirectly prompting his audience to take actions and legitimately change the existing government of the ruling party through the power of the ballots.
Keywords: Pragmatics,SpeechActs,Politics,EndorsementLetter